MENINGKATKAN KETERAMPILAN KOMUNIKASI VERBAL SISWA MELALUI OPTIMALISASI PENGAMATAN OBJEK GAMBAR DALAM PEMBELAJARAN IPA KELAS VIII2 MTs N ANDALAN PEKANBARU - Mutiara Ismet; Zulirfan Zulirfan; Zuhdi Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrak : This class action research was conducted with the effort to improve science process skills grade VIII2 MTs N Andalan Pekanbaru on aspects of verbal communicate through optimization of observation of objects picture with implementation in learning science. This study refers to Taggart and Kemmis model. The instruments used in this research is writing for prasiklus communications test, the cycle I and cycle II as well as oral communication observation sheet for cycles I and II. Based on the analysis of data obtained as a result of prasiklus in the written communication skills of students is still low, that is less then 50%. After the applied action on cycle I of the written communication skills of students increased significantly, that is 74,67%. Follow-up on action taken on the cycle II written skills students also increased to 79,01%. Likewise with oral communication in the first cycle obtained oral communication skills of students is low that is 65.63%, after the given action on the second cycle oral communication skills of students increased to 78.19%. So communication skills of students in the class VIII2 MTs N Andalan Pekanbaru in both written and spoken can be improved by optimizing the media image of the object of science in scientific learning with Light subject matter.Keywords: communication skills, scientific learning, science process skills